MENGUKUR KINERJA KEUANGAN PERUSAHAAN MENGGUNAKAN ANALISIS DU PONT SYSTEM DENGAN MS. ACCESS PROGRAMMING - Suhartono, Suhartono (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2013)
Competition higher business world requires companies to further improve their performance in order to continue to compete and survive. To measure the performance of the company can be seen from the annual financial statements. One of the tools for measuring the financial performance of the company is to use the analysis du pont system. Du Pont Analysis System is an analysis that includes activity ratios and profit margins on sales to determine the profitability of the company which aims to determine the efficiency of the use of corporate assets. In these analyzes used Du Pont chart that serves as a chart designed to show the relationship between the return on the investment, asset turnover and profit margin. Du Pont system can be used by the management company to analyze how to improve performance. One of the advantages Du Pont System is to measure the profitability of each product produced by the company so as to know which product potential. Ms. Access Programming as an application programming can be used to simplify the analysis du pont system.